PENGARUH PENAMBAHAN ABU SEKAM PADI DAN ABU TERBANG BATUBARA TERHADAP KEKUATAN TEKAN DAN POROSITAS GENTENG TANAH LIAT KABUPATEN PRINGSEWU - Kuncoro, Doni Sigit; Tarkono, .; Zulhanif, . (Jurnal Ilmiah Teknik Mesin FEMA, 2013)
Rice husk ash and prosperous coal fly ash silica (SiO2). Silica-term construction, concrete technology  has been used primarily as an additive. Husk ash and coal fly ash is used as an additive clay roof tile manufacturing process. It is made by compounding of clay, sand, water and husk ash. Then, they are mashed by extruder machine and forming of kuweh and then, airing for three days before the process of stamping. The roof tile is dried for four days then there is fumigation for twelve days and continued by combustion for also twelve days. The examination which used is press and porosity examination with the aim of knowing whether there is additional impact of rice’ husk ash’ existence or not into clay roof tile in Kabupaten Pringsewu. The research’s results showed that there is conversion of press and porosity power compared with roof tile rice’s husk ash composition. The optimum value for the press and examination of porosity obtained from the tile with a composition of 5% rice husk ash and 5% coal fly ash 'with an average of 12.253 KPa press strength and porosity values average value of 18.06%. The minimum value for the press obtained from the tile with a composition of 5% rice husk ash and 2,5% coal fly ash with the press power’s average value 9.757 KPa. The minimum value for porosity from the tile with a composition of 5% rice husk ash and 7,5% coal fly ash with the porosity average value 23.78%. Keywords: clay roof tile, rice husk ash, fly ash, silica (SiO2), press power, porosity.